Biomechanical effects of posterior pedicle screw-based instrumentation using titanium versus carbon fiber reinforced PEEK in an osteoporotic spine human cadaver model. (December 2020) - Oikonomidis, Stavros; Greven, Johannes; Bredow, Jan; Eh, Madita; Prescher, Andreas; Fischer, Horst; Thüring, Johannes; Eysel, Peer; Hildebrand, Frank; Kobbe, Philipp; Scheyerer, Max Joseph; Herren, Christian
Abstract: Background: Aim of this biomechanical investigation was to compare the biomechanical effects of a carbon fiber reinforced PEEK and titanium pedicle screw/rod device in osteoporotic human cadaveric spine. Methods: Ten human fresh-frozen cadaveric lumbar spines (L1-L5) have been used and were randomized into two groups according to the bone mineral density. A monosegmental posterior instrumentation (L3-L4) using titanium pedicle screws and rods was carried out in group A and using carbon fiber reinforced PEEK in group B. A cyclic loading test was performed at a frequency of 3 Hz, starting with a peak of 500 N for the first 2000 cycles, up to 950 N for 100, 000 cycles under a general preload with 100 N. All specimens were evaluated with regard to a potential collapse of the implanted pedicle screws. A CT supported digital measurement of cavities around the pedicle at 3 defined measuring points was performed. Finally, the maximum zero-time failure load of all specimens was determined using a universal testing machine (80% Fmax ). Findings: Regarding maximum axial force (group A: 2835 N, group B: 3006 N, p = 0.595) and maximum compression (group A: 11.67 mm, group B: 15.15 mm, p = 0.174) no statistical difference could be shown between the two groups. However, significant smaller cavity formation around the pedicle screws could be observed in group B ( p = 0.007), especially around the screw tip ( p < 0.001). Interpretation: Carbon fiber reinforced PEEK devices seem to be advantageous in terms of microscopic screw loosening compared to titanium devices. Highlights: Biomechanical study of carbon fiber reinforced PEEK and titanium instrumentations. Carbon fiber reinforced PEEK leads to less microscopic screw loosening. Carbon fiber reinforced PEEK shows biomechanical advantages in osteoporotic spine.